مطالعاتِ قرآنی میں چکوال کےاہل علم کی تحقیقات:تحقیقی مطالعہ: Research work by scholars from Chakwal in Quranic studies - malik, Dr Abdul Ghafoor (Pakistan Journal of Qur’ānic Studies, 2024)
Chakwal district of Rawalpindi division has a distinguished position from academic and military point of view. Chakwal has deep roots in history.when arian invaded Indian Subcontinent from central Asia.They crossed the Hindukash mountain and Indus river.They inhabited a larg city at Katas.It became the cultural center of this region۔This region remained center of various fields of knowledge and craftsmanship.A university of linguistics was established in this region.This university remained there until the perid of Mahmood Ghaznavi.The famous geographer Alberuni learned Sanskrit from this university.In 1849,after British accession over Punjab,when Chakwal became a tehsil of district Jehlum .This region remained a center of loacal and foreigner scholars.They founded mosques and madaris and introduced courses in Hifz –e-Quran,Tafseer,Hadith,Fiqh and Arabic grammar.Scholars wrote books to spread Islamic teachings and worked on translations,interpretations and Quranic Studies both in speaking and writing.The first work found in this regard is penned by Qazi Abdul Haleem .He arranged a brief index of quranic teachings.Maulana Muhammad Hassan Faizi elaborated Surah Al Fateha in in Arabic.In the 20 th century ,Maulana Qazi Saad ul din explained those verses of Quran in which the words Allah loves and Allah does not love.After Chakwal became A district in 1985,many scholars rendered their services in this regard.They translated the Holy Quran in Urdu and English.No collaborated work about these research efforts have been published by any research scholar,that is why this topic has been selected in order to highlight the services of scholars in translations,interpretations and Studies of the Holy Quran.